Utility of Contrast-Enhanced Magnetic Resonance Angiography for Delayed Intracranial In-Stent Stenosis in Nonatherosclerotic Cerebral Vascular Diseases - Kannath, Santhosh Kumar; Rajan, Jayadevan Enakshy; Harsha, Kamble Jayaprakash (Journal of Clinical Interventional Radiology ISVIR, 2017)
Noninvasive imaging modalities are being used for long-term follow-up of intracranial stented patients of nonatherosclerotic etiology. The aim of this study is to determine the utility of contrast-enhanced magnetic resonance angiography (CE-MRA) source images in delayed intracranial in-stent stenosis. A total of 18 stented patients for nonatherosclerotic etiology were reviewed; all had follow-up digital subtraction angiography (DSA) and CE- and time-of-flight (TOF)-MRA. Four sets of MR images (TOF-MRA reformatted images, TOF-MRA source images, CE-MRA reformatted images, and CE-MRA source images) were reviewed for detection of ≥ 50% stenosis. Accuracy of each image set was calculated comparing to DSA. Overall delayed in-stent stenosis during follow-up DSA was 10%. The sensitivity of TOF reformatted image, TOF source image, CE-MRA reformatted image, CE-MRA source image are 33% (6/18), 55.6% (10/18), 77.8% (14/18), and 100% (18/18), respectively, while negative predictive value are 14.3% (2/14), 20% (2/10), 33% (2/6), and 100% (2/2), respectively. CE-MRA source images are equally efficacious as DSA to detect significant (≥ 50%) delayed in-stent stenosis.
Keywords: intracranial stent; in-stent stenosis; magnetic resonance angiography; MRA; digital subtraction angiography